Teaching Syntax in the Digital Age: Tools and Techniques for Educators - Fadilla, Faris; Hsb, Juanda Muktar; Putri, Nadila Adelia; Ahwani, Sahfitri; Nasution, M. Habib Rifky; Ismahani, Siti (International Journal of English Education and Linguistics (IJoEEL), 2024)
This paper explores contemporary approaches to teaching syntax in the digital era, examining how technology integration and modern pedagogical methods can enhance students' understanding of linguistic structures. The research investigates various digital tools, interactive platforms, and innovative teaching strategies that effectively support syntax instruction in both traditional and virtual learning environments. Through a comprehensive analysis of recent studies and practical applications, this paper provides educators with evidence-based recommendations for incorporating digital resources into syntax instruction while maintaining pedagogical effectiveness.